The Flouting Maxim on Twitter Influencers’ Tweets - Nibros Hassani (Journal of Pragmatics Research, 2019)
This study aims to discover the use of maxim principles on the tweets that made by certain of Indonesian social-media influencers which the method is conducted qualitatively. The data is taken from Twitter.com and Twitter App, where the researcher captured the tweets randomly and analyzed it by using maxim relevance principle as the tool of analysis. The result shows vary: most of the conversations were not obeying the maxim of relevance principles, or in other words do not imply maxim of relevance principle. Moreover, the intentions are to make jokes, and to run the conversation smoothly while doing the flouting.Keywords: maxim of relevance, twitter, social media influencer